2021
DOI: 10.1021/acs.chemrestox.1c00287
|View full text |Cite
|
Sign up to set email alerts
|

4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone-Induced Histone Acetylation via α7nAChR-Mediated PI3K/Akt Activation and Its Impact on γ-H2AX Generation

Abstract: A typical tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is known as a strong carcinogen. We previously reported that metabolized NNK induced histone H2AX phosphorylation (γ-H2AX), a DNA damageinduced histone modification. In this study, we found that NNK globally acetylated histone H3, which affected γ-H2AX generation. Human lung adenocarcinoma A549 was treated with several doses of NNK. NNK induced dose-dependent global histone H3 acetylation (Ac-H3), at 2 to 12 h after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…(Figure 8) In this study, the PI3K/AKT/mTOR pathway was activated to repair damaged DNA during UVA irradiation but was not significantly activated by MF treatment. In contrast, MF repaired damaged DNA by reducing the expression levels of γH2AX and phosphorylated ATM, whereas MF reduced DNA damage by reducing oxidative stress in cells [32]. The reduction in DNA damage inhibits the activation of PIKK, thereby inhibiting the initiation of PI3K/AKT/mTOR signaling [33].…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 8) In this study, the PI3K/AKT/mTOR pathway was activated to repair damaged DNA during UVA irradiation but was not significantly activated by MF treatment. In contrast, MF repaired damaged DNA by reducing the expression levels of γH2AX and phosphorylated ATM, whereas MF reduced DNA damage by reducing oxidative stress in cells [32]. The reduction in DNA damage inhibits the activation of PIKK, thereby inhibiting the initiation of PI3K/AKT/mTOR signaling [33].…”
Section: Discussionmentioning
confidence: 99%
“…26 We previously showed that the DNA adduct formation by 4-(methylnitrosamino)-1-(3pyridyl)-1-butanone can be evaluated by γ-H2AX. 29 Several kinds of DNA adducts including BaP metabolites can generate γ-H2AX, and multiple kinases including ATM, ATR, and DNAdependent protein kinase (DNA-PK) seem to be involved in the induction. 30 BPDE, an oxidized form of BaP produced via metabolic processes including CYP1A1, is considered to be the one to contribute to the γ-H2AX generation by forming DNA adducts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…γ-H2AX was originally identified as an early event after the direct formation of DNA double-strand breaks (DSBs) by ionizing radiation. , H2AX is also phosphorylated by DSBs formed indirectly by the collision of replication forks at sites of DNA damage and single-strand breaks (SSBs) formed in the repair process via ataxia telangiectasia mutated (ATM) and ATM and Rad3-related (ATR) activation . We previously showed that the DNA adduct formation by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone can be evaluated by γ-H2AX . Several kinds of DNA adducts including BaP metabolites can generate γ-H2AX, and multiple kinases including ATM, ATR, and DNA-dependent protein kinase (DNA-PK) seem to be involved in the induction .…”
Section: Introductionmentioning
confidence: 99%